2020
DOI: 10.1519/jsc.0000000000003881
|View full text |Cite
|
Sign up to set email alerts
|

Acute Performance Enhancement Following Squats Combined With Elastic Bands on Short Sprint and Vertical Jump Height in Female Athletes

Abstract: Krčmár, M, Krčmárová, B, Bakaľár, I, and Šimonek, J. Acute performance enhancement after squats combined with elastic bands on short sprint and vertical jump height in female athletes. J Strength Cond Res 35(2): 318–324, 2021—The main purpose of this study was to compare back squats with and without elastic bands on sprint and vertical jump height. Fourteen female athletes (21.9 ± 2.3 years; 177.5 ± 6.36 cm; 66.2 ± 6.2 kg; 1 repetition maximum [1RM]/ body mass: 1.96 ± 0.14) agreed to participate. On 4 separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…To ensure similar loading across both groups, half of the variable resistance (17% 1RM) was removed from the free-weight in the VRT group, as previously reported ( Krčmár et al, 2021 ; Mina et al, 2019 ). In addition, when adjusting the intensity of the back squat throughout the intervention, the contribution of variable resistance remained constant and only the free-weight varied in the VRT group ( Andersen et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure similar loading across both groups, half of the variable resistance (17% 1RM) was removed from the free-weight in the VRT group, as previously reported ( Krčmár et al, 2021 ; Mina et al, 2019 ). In addition, when adjusting the intensity of the back squat throughout the intervention, the contribution of variable resistance remained constant and only the free-weight varied in the VRT group ( Andersen et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Given that muscle activation partly underpin PAPE (Tillin and Bishop, 2009), it might be hypothesized that a higher contribution of variable resistance in VRT may better potentiate subsequent power performance. This notion is somewhat supported in the research whereby a 30% VRT condition (30% of the total load (85% 1repetition maximum (RM)) induced a greater PAPE in selective power outcomes than 20% VRT conditions (Krčmár et al, 2021). However, another study using similar loading reported no significant between-group differences in all posttests (Wyland et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Among these studies, those that compared AR with traditional BS and BP after multiple weeks of application observed increases in power, RFD, or maximal strength (1,2,6,9,14). However, the current investigators are aware of only 1 AR study having been conducted in a female only cohort, and it implemented an acute postactivation potentiation protocol (8). Owing to the physiological differences between males and females (i.e., muscle fiber composition and density, fatigue rates, recovery capacity, etc), results of previous research in alternative cohorts cannot be extrapolated to trained females.…”
Section: Introductionmentioning
confidence: 99%
“…In Drinkwater et al, 2005;Izquierdo et al, 2006;Latella et al, 2019;Lawton et al, 2004) ประกอบกั บมี งานวิ จั ยจำนวนมากค้ น พบว่ าการฝึ กทั ้ งสองรู ปแบบสามารถเพิ ่ มสมรรถภาพหลั งการกระตุ ้ นได้ ดี (Iacono et al, 2019;Israetel et al, 2010;Krcmár et al, 2021;Nickerson et al, 2018;Wyland et al, 2015) ผู Comfort et al, 2015;Garhammer, 1982;Haff et al, 2003;Hydock, 2001;Kawamori et al, 2006;Macke, 2018) (Everett, 2012)…”
unclassified